Confirmatory double-blind, parallel-group, placebo-controlled study of efficacy and safety of edaravone (MCI-186) in amyotrophic lateral sclerosis patients. Issue 7 (December 2014) - Abe, Koji; Itoyama, Yasuto; Sobue, Gen; Tsuji, Shoji; Aoki, Masashi; Doyu, Manabu; Hamada, Chikuma; Kondo, Kazuoki; Yoneoka, Takatomo; Akimoto, Makoto; Yoshino, Hiide; on behalf of The Edaravone ALS Study Group
Abstract Our objective was to confirm the efficacy and safety of edaravone in amyotrophic lateral sclerosis (ALS) patients. We conducted a 36-week confirmatory study, consisting of 12-week pre-observation period followed by 24-week treatment period. Patients received placebo or edaravone i.v. infusion over 60 min for the first 14 days in cycle 1, and for 10 of the first 14 days during cycles 2 to 6. The efficacy primary endpoint was changed in the revised ALS functional rating scale (ALSFRS-R) scores during the 24-week treatment. Patients were treated with placebo (n = 104) and edaravone (n = 102). Changes in ALSFRS-R during the 24-week treatment were −6.35 ± 0.84 in the placebo group (n = 99) and −5.70 ± 0.85 in the edaravone group (n = 100), with a difference of 0.65 ± 0.78 (p = 0.411). Adverse events amounted to 88.5% (92/104) in the placebo group and 89.2% (91/102) in the edaravone group. In conclusion, the reduction of ALSFRS-R was smaller in the edaravone group than in the placebo group, but efficacy of edaravone for treatment of ALS was not demonstrated. Levels and frequencies of reported adverse events were similar in the two groups.